AKTIVITAS BELAJAR SISTEM DARING SISWA DI SMA NEGERI 1 BAHODOPI PADA MASA PANDEMI COVID-19 - Yulia Windarsih Windarsih; Manap Trianto; M. Abimanyu (Koordinat Jurnal MIPA, 2022)
This study aims to explain the online learning activities of students at SMA Negeri 1 Bahodopi during the Covid-19 pandemic. This type of research is descriptive research. The population of this study were students of class X, XI and XII MIPA at SMA Negeri 1 Bahodopi. The sample in this study amounted to 66 students who were determined by the quota sampling technique. Data collection techniques using a questionnaire. The results of online system learning activitiesStudents during the Covid-19 pandemic were seen from 7 indicators, namely 1) visual activities obtained a percentage of 61.03%. 2) oral activities obtained a percentage of 66.8%. 3) listening activities obtained a percentage of 72.03%. 4) writing activities get a percentage of 70.15%. 5) drawing activities obtained a percentage of 76.05%. 6) mental activities obtained a percentage of 63, 03%. 7) emotional activities get a percentage of 75.06%. From this research it can be concluded that of the 7 indicators have enough categories with an average percentage of 69.16%.